2007
DOI: 10.1029/2006wr005233
|View full text |Cite
|
Sign up to set email alerts
|

Riparian hydroecology: A coupled model of the observed interactions between groundwater flow and meadow vegetation patterning

Abstract: [1] Stream incision is altering the hydroecology of riparian areas worldwide. In the Last Chance watershed in the northern Sierra Nevada, California, logging, overgrazing, and road/railroad construction have caused stream incision, which resulted in drainage of riparian meadow sediments and a succession from native wet meadow vegetation to sagebrush and dryland grasses. Restoration efforts have been initiated to reestablish the ecosystem function of these systems. Original field data including stream stage rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
148
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(155 citation statements)
references
References 41 publications
6
148
0
1
Order By: Relevance
“…There are over 30 communities in the entire project area, with an estimated 49.3 km 2 of total land area affected by restoration activities after accounting for regeneration rates in NonProject communities. Other wet meadow restoration studies found that grade control structures that accumulate sediment in incised gullies raised water tables and contributed to vegetation recovery in a buffer zone up to 100-m on either side of the channel (Shields et al 1995;Schilling et al 2003;Loheide & Gorelick 2007;Loheide & Booth 2011). We speculate that check dams affect bofedal and grassland vegetation in a broader area by raising water tables relative to surface vegetation, a conclusion that deserves further research.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…There are over 30 communities in the entire project area, with an estimated 49.3 km 2 of total land area affected by restoration activities after accounting for regeneration rates in NonProject communities. Other wet meadow restoration studies found that grade control structures that accumulate sediment in incised gullies raised water tables and contributed to vegetation recovery in a buffer zone up to 100-m on either side of the channel (Shields et al 1995;Schilling et al 2003;Loheide & Gorelick 2007;Loheide & Booth 2011). We speculate that check dams affect bofedal and grassland vegetation in a broader area by raising water tables relative to surface vegetation, a conclusion that deserves further research.…”
Section: Discussionmentioning
confidence: 96%
“…Land degradation impacts bofedales in the study area through the following mechanisms: (1) reduced vegetative cover, increased runoff, and decreased infiltration rates on slopes reduce groundwater recharge, causing dry season water stress for wetland plants (Trimble & Mendell 1995;Salvador et al 2014); (2) gullies that incise through bofedales lower water tables, changing species composition, also causing dry season water stress for wetland plants (Wright & Chambers 2002;Schilling et al 2003;Loheide & Gorelick 2007;Loheide & Booth 2011); (3) increased flow velocities in channels can increase vegetation scour, leading to rapid development and destruction of bofedal vegetation in channels and floodplains (Earle et al 2003); and (4) increased sediment transported from slopes can cover bofedales that are not incised by gullies, causing plant mortality, changes in species composition, and increased soil elevation relative to the water table (Werner & Zedler 2002;Miller et al 2012).…”
Section: Methods Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Feedbacks related to water use by a particular plant functional type influencing hydrology and subsequently impacting the composition of plant functional types are important at other floodplain sites [e.g., Loheide and Gorelick, 2007]. This feedback is central to the discipline of ecohydrology, which studies the two-way interaction between water and ecosystems [Hannah et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers have simulated these processes using physically based saturated [Lowry et al, 2011;Rains et al, 2004;Springer et al, 1999] and variably saturated [Hammersmark et al, 2010;Loheide and Booth, 2011;Loheide and Gorelick, 2007] groundwater flow models to generate predictions of water table depth that are then linked with vegetation models to provide quantitative predictions of vegetation composition. Although modeling techniques varied among these previous studies, all used groundwater metrics as predictor variables.…”
Section: Introductionmentioning
confidence: 99%